Baseline (derived) neutrophil-lymphocyte ratio associated with survival in gastroesophageal junction or gastric cancer treated with ICIs - Yu, Chengyang; Jiang, Hao; Wang, Liezhi; Jiang, Zufu; Jin, Chong (Frontiers in Oncology, 2025)
ObjectiveWe carried out the meta-analysis to determine the predictive value of baseline neutrophil to lymphocyte ratio (NLR) and derived neutrophil to lymphocyte ratio (dNLR) levels in patients with gastroesophageal junction or gastric cancer (GJGC) who underwent immune checkpoint inhibitor (ICI) treatment.MethodsEligible articles were obtained through PubMed, the Cochrane Library, EMBASE, and Google Scholar, until April 15, 2023. The clinical outcomes evaluated in this study encompassed overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and disease control rate (DCR)ResultsA total of 24 articles with 2221 patients were included in this meta-analysis. The pooled results demonstrated that patients with high NLR levels had significantly poorer OS (HR: 1.860, 95% CI: 1.564-2.213, p < 0.001) and PFS (HR: 1.678, 95% CI: 1.354-2.079, p < 0.001), and lower ORR (OR: 0.754, 95% CI: 0.621-0.915, p = 0.004) and DCR (OR: 0.391, 95% CI: 0.262-0.582, p < 0.001). Besides, we also found that high dNLR levels were significantly associated with shorter OS (HR: 2.117, 95% CI: 1.590-2.820, p < 0.001) and PFS (HR: 1.803, 95% CI: 1.415-2.297, p < 0.001).ConclusionLow baseline (Derived) NLR has the potential to predict the good efficacy of ICIs and survival outcomes in patients with GJGC. (Derived) NLR could be useful in determining the optimal treatment strategies for these patients.